2020
DOI: 10.4067/s0717-95022020000100140
|View full text |Cite
|
Sign up to set email alerts
|

Safety Ranges in V3 Segment of the Vertebral Artery for Surgical Procedures at the Craniocervical Junction

Abstract: The aim of this study was to establish safety ranges for the third vertebral artery segment (V3) for craneocervical procedures. Injury to V3 represents a potentially catastrophic complication. Its tortuous path and complex relationship with neighboring structures, increasing the risk. Ten male adult cadavers (20 vertebral arteries) with arterial infiltration of red latex were studied. The length, angles and anatomical measurements were obtained between the selected surgical landmarks and the portions of V3 seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Cacciola et al reported that the distance of the tip or the most medial part of the VA osseous segment from the midline of the C2 body ranged from 6.1 to 16.2 mm (11.7mm average) from an anterior transoral surgical view. Cruz-Elizondo et al recorded the distance between C2 spinous process towards the medial edge of the most prominent point of the proximal loop as 43.8±4.2 mm [ 5 ]. Güvençer M et al carried out an angiographic study in 12 human cadavers and reported that the distance between the VA's medial side of the V2 segment related to the axis and the midline was 17.6±6.1 on the right side and 14.7±2.1 on the left.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cacciola et al reported that the distance of the tip or the most medial part of the VA osseous segment from the midline of the C2 body ranged from 6.1 to 16.2 mm (11.7mm average) from an anterior transoral surgical view. Cruz-Elizondo et al recorded the distance between C2 spinous process towards the medial edge of the most prominent point of the proximal loop as 43.8±4.2 mm [ 5 ]. Güvençer M et al carried out an angiographic study in 12 human cadavers and reported that the distance between the VA's medial side of the V2 segment related to the axis and the midline was 17.6±6.1 on the right side and 14.7±2.1 on the left.…”
Section: Discussionmentioning
confidence: 99%
“…It then runs in a groove present on the superior surface of the posterior arch of the atlas. The fourth segment of the artery crosses the atlantooccipital membrane and enters the cranial cavity [ 4 , 5 ]. As the VA ascends cranially, the transverse foramen moves from an anterolateral to a posteromedial position [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations